Towards a historical geography of Gerês / Xurés: the making of a cross-border region - Paül, Valerià; Trillo Santamaría, Juan M. (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
The Gerês/Xurés region is located in the central area of the Galician-North Portuguese borderlands. The territory encompasses two parks: a national park in Portugal, and a natural park in Galicia. In this article, a historical geography of the area, under the theoretical framework of cross-border region. The methods combine fieldwork (semi-structured interviews) and analysis of different sources: books, official documents, articles, web pages and archives.
Keywords: Historical geography; territory; boundary; crossborder región; Transboundary Protected Area (TBPA); Galicia/Portugal